Analisis Kerusakan Telepon Pada Voice Control Unit (VCU) Pada Perum LPPNPI Kantor Cabang Manado - Octavianie, Adhitya; Adi Putra, Aqram (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Voice Communication Control System (VCCS) is a tool designed to make it easier for users to communicate voice by integrating all users (clients) and means of communication in one system and controlled using a control panel. VCCS is a voice switching device used in VHF A / G and Direct Speech communications. The benefit of using VCCS is that when the user makes flight communication it becomes easy because all frequencies and telephones are combined in a VCU (Voice Control Unit) so that the ATC desk/work desk is not filled with communication devices. In addition, to facilitate its use, the VCCS client control panel uses a touch screen system. AirNav Indonesia Manado Branch has a LESS brand VCCS equipment server manufactured by China. VCCS consists of two main parts, namely the server and client. The server is a processing center and control center for switching input and output, while the client or VCU (Voice Control Unit) is the device used by the user in VCCS operations. There are 7 VCUs at AirNav Indonesia Manado which are placed in the Tower room (3 VCU), APP room (3 VCU), and FSS Kompen room (1 VCU).